Lipid Rafts Disruption Increases Ochratoxin A Cytotoxicity to Hepatocytes. Issue 2 (25th August 2015) - Zhang, Yu; Qi, Xiaozhe; Zheng, Juanjuan; Luo, Yunbo; Zhao, Changhui; Hao, Junran; Li, Xiaohong; Huang, Kunlun; Xu, Wentao
ABSTRACT: Lipid rafts are microdomains in plasma membrane and can mediate cytotoxicity. In this study, the role of lipid rafts in ochratoxin A‐induced toxicity was investigated using Hepatoblastoma Cell Line HepG‐2 cells. Disruption of cholesterol‐containing lipid rafts enhanced Ochratoxin A (OTA) toxicity, as shown by increased lactate dehydrogenase leakage, increased reactive oxygen species level and reduction of superoxide dismutase activity in a time‐dependent manner. Isobaric tags for relative and absolute quantitation‐based proteomics of the cell membranes showed that nearly 85.5% proteins were downregulated by OTA, indicating that OTA inhibited the membrane protein synthesis. Most of altered proteins were involved in Gene Ontology "transport", "cell adhesion" and "vesicle‐mediated transport". In conclusion, lipid rafts play a key role in OTA‐induced cytotoxicity. This study provides insight into how OTA toxicity is regulated by the plasma membrane, especially the lipid rafts.